KEBUDAYAAN DAN PEMBANGUNAN DAERAH (Sebuah Refleksi Kebangkitan Nilai) - Simon Sabon Ola (Jurnal Lazuardi, 2021)
This paper discusses about several cultural aspects of culture that can be used as a foundation for regional development. The facts show that cultural based development is not yet holistic. There are many cultural values ​​that are neglected in regional development. At least four aspects of development that can take advantage of local-traditional culture, namely: matters of livelihood, matters of government, politics, and matters of religion and belief in God Almighty. The presentation of facts regarding the four things mentioned above is a reflection of the revival of values. This reflection would spur all government policy to take advantage of aspects of local culture as a material consideration in designing and implementing development in the region.